AB0262 Searching predictors of abatacept efficacy in patients with rheumatoid arthritis. (12th June 2018) - Borisova, M.; Lukina, G.; Sigidin, Y.; Aronova, E.; Luchihina, E.; Karateev, D.; Novikov, A.; Alexandrova, E.; Cherkasova, M.; Glukhova, S.; Nasonov, E.
Abstract : Background: Biologics have revolutionised the treatment of rheumatoid arthritis (RA). Several types of biologics are used in clinical practice, one of them is the blocker of T cells co-stimulation – abatacept (ABA). The search for predictors of biologics efficacy is an important issue in current rheumatology practice. Objectives: To identify predictors of ABA efficacy based on the analysis of various serum biomarkers changes. Methods: 44 RA pts with a history of previous DMARDs and biologics failures and 16 healthy donors as controls were included in the study. The majority of pts were females, RF-positive – 80%, anti-CCP-positive – 79, 5%, mean age 49.6±13.9 years, median disease duration 2 1, 4;3 years, with high RA activity (mean DAS28=5, 2±0, 8). Enzyme-linked immunoassay was used to measure serum concentrations of biomarkers IL-1β, IL-6, IL-17AF, TNF-α, VEGF-A, IP-10, YKL-40, MMP3 at baseline and after 6 months of ABA therapy. Disease activity was assessed every 3 months using DAS28. ABA were administered IV according to standard schedule. Results: RA pts had significantly increased levels of IL-6 (2.4 [1.1–6, 4] vs 0.7 [0, 62–1, 0] pg/ml, p=0, 0002), YKL-40 (97 68, 4–97, 9 vs 64 52, 4–107, 5 pg/ml, p=0.03), and IP-10 (21 12, 9–49, 8 vs 14 9, 2–15, 2 pg/ml, p=0.005) compared to the control group. By the 6-th month ABA significantly reduced the levels of IL-6 up to 1.29 [0, 9–2, 2] pg/ml, p=0.0006 and IP-10 – to 14 7, 5–28 pg/ml, p=0.007, as well as MMP3 and RF from 30.1 13–82 to 10 [7.4–55] pg/ml, p=0.0003) and from 218 [9.6–187] to 159 [9.7–155] pg/ml, p=0.02), respectively. There was a significant correlation between the decrease of IL-6 (r=0.5) and IP-10 (r=0, 32) levels and decrease of DAS28 scores (p<0.05). A trend to a more pronounced reduction in disease activity was identified in anti-CCP-positive and anti-MCV-positive pts. By EULAR criteria the percentage of no-responders among anti-CCP-negative and anti-MCV-negativ e was almost two times higher as compared to antibodies-positive pts, i.e., 27.2% vs 16% and 26.7% vs. 14.8%, respectively, although the difference failed to reach statistical significance. However, by 6 months the percentage of pts with high disease activity among anti-MCV-negative pts were significantly higher than among anti-MCV-positive (20% and 0%, p=0.03, respectively). Higher baseline IL-6 (p=0.03) and YKL-40 (p=0.02) levels were registered among non-responders to ABA therapy. Conclusions: ABA therapy led to a significant reduction in concentrations of pro-inflammatory IL-6 and IP-10 cytokines, as well as of MMP3 and RF. The decrease of IL-6 and IP-10 levels significantly correlated with the decrease of RA activity. There was a trend towards more pronounced reduction of disease activity in anti-CCP-positive and anti-MCV-positive pts. High baseline IL-6 and YKL-40 levels were significantly more frequently registered among non-responders. Therefore, anti-MCV-negativity, high baseline levels of IL-6 and YKL-40 could be used as predictors of insufficient ABA efficacy in this category of pts. A small sample of pts is the major limitation of this study, requiring future studies. Disclosure of Interest: None declared